Inclusive early childhood education : development, resources, practice - Deiner, Penny Low. (Belmont, CA : Wadsworth Cengage Learning, 2013)
This book is a comprehensive special education resource book that provides essential information on a variety of early childhood learning disabilities, as well as strategies for including children with these special needs in regular educational settings. The author provides you with a solid grounding in theory and research as well as practical guidelines, real-world vignettes, and hands-on program planning assistance to prepare you to integrate children with learning disabilities into your classrooms. Updated throughout, this edition also introduces videos that are available for viewing at the Early Childhood Education Media Library, allowing you to see text concepts brought to life in real classroom settings. Whether you're training to be a pre-school teacher, kindergarten teacher, early education provider, child care provider, or administrator in any of these settings, you'll keep this resource with you long after you complete your coursework.
Includes bibliographical references
Keywords: Early childhood education; Inclusive education